Metode Bimbingan Belajar di Primagama (Studi Deskriptif di Lembaga Bimbingan Belajar Primagama) - Eko Riyanti; Abdul Khoir HS (Turats, 2011)
This study describes the method tutoring in Primagama which was held at the Institute Tutoring Primagama Kemang Pratama Bekasi. The purpose of this study is to determine the methods applied in the Institute Tutoring Primagama Kemang Pratama Bekasi. Benefits for students who follow the guidance study at the Institute Tutoring Primagama Kemang Pratama Bekasi is that students should be able to know the smart solution method taught by professional tutors, tutor, powerful in its field. In the implementation methods tutoring, tutors provide practice exam questions (try out). The purpose of this study was to determine the method of tutoring smart solution implemented at the Institute Tutoring Primagama Kemang Pratama Bekasi. This research was conducted at the Institute Tutoring Primagama Kemang Pratama Bekasi. This research method is to use a qualitative method of naturalistic, with procedures for data collection using observation, interviews, and study documentation. Data analysis was done qualitatively by way of interpretation and describes a holistic and logic against the data received. Results showed that students were satisfied and willing to learn by following the guidance of learning at the Institute Tutoring Primagama Kemang Pratama Bekasi. It is evident that students arevery enthusiastic and more confident doing exam questions are considered difficult